2005
DOI: 10.1080/01421590500097075
|View full text |Cite
|
Sign up to set email alerts
|

Open book tests: assessment of academic learning in clerkships

Abstract: An examination of an open-book testing approach in a family medicine clerkship seeks to determine whether this method more closely mirrors the discipline of family medicine, where practitioners refer daily to written resource materials in order to make clinical decisions without compromising the learning and assessment process. Student scores on the multiple-choice test were analysed by year, by quarter and by site using ANOVA. Students in the experimental site were interviewed to determine preparation style, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 8 publications
8
76
0
Order By: Relevance
“…The focus group suggested that when preparing for open-book assessment, the layout of the textbook should be studied and arranged by using markers, flags and highlights. The importance of preparing the material in this way is confirmed by the findings by Broyles et al (2005). When it comes to the positive effects of the referencing habit, research has shown that maintaining a referencing habit while preparing for an open-book assessment is essential, but during an open-book assessment it should be used sparingly, and only as a back-up (Boniface, 1985;Jacobs, 1990).…”
Section: Discussion On the Affinity 'Good Preparation'mentioning
confidence: 58%
See 4 more Smart Citations
“…The focus group suggested that when preparing for open-book assessment, the layout of the textbook should be studied and arranged by using markers, flags and highlights. The importance of preparing the material in this way is confirmed by the findings by Broyles et al (2005). When it comes to the positive effects of the referencing habit, research has shown that maintaining a referencing habit while preparing for an open-book assessment is essential, but during an open-book assessment it should be used sparingly, and only as a back-up (Boniface, 1985;Jacobs, 1990).…”
Section: Discussion On the Affinity 'Good Preparation'mentioning
confidence: 58%
“…Broyles et al (2005) concur by stating that being aware of time is vitally important. Time plays a role during preparation, while writing the assessment and when using the textbooks (tools) available during the assessment.…”
Section: Discussion On the Affinity 'Time Management'mentioning
confidence: 91%
See 3 more Smart Citations